Application of Neural Network Methods in RS-based Thematic Mapping; 5th AGILE Conference on Geographical Information Science, Palma (Balearic Islands, Spain), April 25th - 27th 2002 - Markov N. G. Nikolai Grigorevich (2002, 2002)
В фонде НТБ ТПУ отсутствует